The Implementation of the Make a Match Cooperative Learning Model to Improve Learning Activeness in IPAS Learning Among Fourth-Grade Elementary School Students - Natriani Syam; Nur Ilmi; Nur Awaliyah Syais (PT. Lontara Digitech Indonesia, 2026)
The problem in this study is the low learning activeness of fourth-grade students. The research problem is how the implementation of the Make a Match cooperative learning model can improve students’ learning activeness in IPAS learning among fourth-grade students at UPTD SD Negeri 9 Parepare. This study is Classroom Action Research (CAR), which aims to determine the process and results of implementing the Make a Match cooperative learning model to improve students’ learning activeness in IPAS learning in Grade IV. The approach used in this study is a qualitative approach. The data collection techniques used were observation and documentation. The data analysis techniques used were data collection, data reduction, data display, and conclusion drawing/verification. The subjects of this study consisted of 27 participants, namely one fourth-grade teacher and 26 students. The study was conducted in two cycles. In Cycle I, the research results showed that the learning process was in the fair qualification (C), and students’ learning activeness was in the moderate category. In Cycle II, the research results showed that the learning process was in the good qualification (B), and students’ learning activeness was in the high category. The conclusion of this study is that the implementation of the Make a Match cooperative learning model can improve the learning process and students’ learning activeness in IPAS learning in Grade IV at UPTD SD Negeri 9 Parepare.